Epoxy resin conductive coating based on carbon nanotube / polyaniline composite modification and preparation method thereof
By using a specific solvent in epoxy resin to dissolve the carbon nanotubes and compounding it with polyaniline, the problems of difficulty in dispersing and poor compatibility of carbon nanotubes in epoxy resin are solved, and high-performance conductive coatings are realized, suitable for new energy, aerospace and other fields.
Patent Information
- Application Number
- CN202411808637.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Carbon nanotubes have difficulties in dispersion in epoxy resin systems, limited improvement in conductivity and mechanical properties, and inability to produce large-scale production. The dispersion method of carbon nanotubes will damage their structure, resulting in reduced conductivity and poor compatibility with epoxy resin.
The carbon nanotubes are initially dissolved in a specific solvent to prepare a uniformly dispersed carbon nanotube dispersion liquid, and then polyaniline is added, evaporated or purified by solvent to prepare a carbon nanotube/polyaniline composite and is compounded with an epoxy resin to obtain an epoxy resin conductive coating based on carbon nanotube/polyaniline composite modification.
The uniform dispersion of carbon nanotubes in epoxy resin is achieved, the conductivity and mechanical properties are enhanced, and the compatibility problem is solved. This method is suitable for solvent-free systems and reduces environmental pollution.
Smart Images

Figure CN119799117A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a carbon nanotube / polyaniline composite-modified epoxy resin conductive coating and a preparation method thereof, belonging to the technical field of coatings. Background Art
[0002] Conductive coatings play an important role in preventing static electricity accumulation and electrostatic discharge (ESD). Epoxy resin, as a matrix material, provides excellent adhesion, chemical resistance and mechanical strength to form a hard protective coating. Adding carbon nanotubes as conductive fillers to epoxy resin can significantly improve the conductivity of the coating. With its excellent conductivity and high strength, a small amount of carbon nanotubes can effectively reduce the surface resistance of the coating and enhance the wear resistance and mechanical strength of the coating.
[0003] When epoxy resin and carbon nanotubes are used in conductive coatings, despite their great performance potential, they face a series of challenges. First, the dispersion problem of carbon nanotubes significantly affects the uniformity and conductivity of the coating, and easily leads to aggregation; ensuring good dispersion of conductive fillers in epoxy resin is the key, and effective dispersion technology and surface treatment methods are required. Secondly, the compatibility problem between epoxy resin and conductive fillers cannot be ignored; if the interface bonding is poor, the physical properties and conductivity of the coating will be affected. Therefore, it is necessary to enhance the interaction between reinforcing materials. In addition, carbon nanotubes can enhance the conductivity of the coating, but how to balance their proportions to achieve optimal performance remains a challenge; excessive use may lead to a decrease in the mechanical properties of the coating, while insufficient use will fail to achieve the expected conductive effect.
[0004] At present, the conventional methods for using carbon nanotubes in epoxy resin systems include solution blending, in-situ polymerization, chemical modification, etc. For example, the literature (Shi Xuejun, Ren Yidan. Thermal conductivity and mechanical properties of carbon nanotube / epoxy resin composites [J]. Journal of Pingdingshan University, 2020, 35(5): 39-42.) adopts a solution blending method, specifically, carbon nanotubes are added to ethanol, ultrasonically dispersed and stirred, epoxy resin is added to the suspension, and then magnetic stirring is performed. When the temperature rises to 60°C, the ethanol in the system is removed by vacuum distillation to obtain a carbon nanotube / epoxy resin composite material; the literature (Yao Meijuan. Functionalization of carbon nanotubes with polyacrylic acid and its application in epoxy resin [D]: [Master's thesis]. Ocean University of China, 2014.) adopts an in-situ polymerization method, specifically, the in-situ polymerization method-precipitation polymerization method is used to functionalize carbon nanotubes with polyacrylic acid to prepare carbon nanotube / epoxy resin. Resin composite materials; the literature (Gao Ruize. Preparation and Mechanical Properties of Functionalized Carbon Nanotube / Continuous Carbon Fiber Multi-scale Reinforced Epoxy Resin Composites [D]: [Master's Thesis]. Beijing University of Chemical Technology, 2021.) is to prepare a mixed acid solution in a ratio of 1:1 between concentrated sulfuric acid and concentrated nitric acid, add a certain amount of carbon nanotubes to the prepared mixed acid solution, gently stir with a glass rod until it is evenly stirred, and heat the mixed solution under reflux to fully oxidize the multi-walled carbon nanotubes to obtain carboxyl carbon nanotubes; this carbon nanotube and epoxy resin are used for compounding to prepare carboxyl carbon nanotube / epoxy resin composite materials; however, in these methods, it is difficult for carbon nanotubes to be evenly dispersed in the epoxy resin system, and the load on the matrix cannot be effectively transferred to the carbon nanotubes, making it difficult to give full play to the excellent performance of carbon nanotubes; and it is difficult to produce on a large scale industrially; in addition, the improvement of the mechanical properties and conductive properties of epoxy resin is limited.
[0005] In addition, the dispersion difficulty of carbon nanotubes, conventional graphene and graphene oxide in epoxy resin systems is different. Graphene oxide is easier to disperse because it contains more active groups on its surface. Graphene is a layered structure, and its dispersion considers the stacking between layers. However, carbon nanotubes are prone to agglomeration and entanglement due to their nano effect, resulting in uneven dispersion at high content.
[0006] In summary, although epoxy resin and carbon nanotube composites show broad application prospects in conductive coatings, challenges in dispersibility, compatibility, conductivity regulation, processing technology, environmental stability, etc. need to be urgently addressed to promote their development in practical applications. Summary of the invention
[0007] [Technical issues]
[0008] Carbon nanotubes are difficult to disperse in epoxy resin systems, have limited improvements in conductivity and mechanical properties, and cannot be mass-produced;
[0009] The dispersion method of carbon nanotubes will destroy the structure of carbon nanotubes to a certain extent, resulting in reduced conductivity; and carbon nanotubes have poor compatibility with epoxy resin.
[0010] [Technical solution]
[0011] In order to solve the above problems, the present invention provides a carbon nanotube / polyaniline composite modified epoxy resin conductive coating and its preparation method. Specifically, the present invention preliminarily disentangles carbon nanotubes through a specific solvent to prepare a uniformly dispersed carbon nanotube dispersion; then polyaniline is added to the carbon nanotube dispersion, and then the solvent is evaporated or purified to prepare a carbon nanotube / polyaniline composite; finally, the carbon nanotube / polyaniline composite is composited with epoxy resin to obtain a high-performance carbon nanotube / polyaniline composite modified epoxy resin conductive coating. The present invention utilizes the efficient and orderly nano-assembly between carbon nanotubes and polyaniline in a specific solvent, which not only makes up for the defect that carbon nanotubes CNT are easy to aggregate into bundles, but also solves the dispersion problem of carbon nanotubes CNT in epoxy resin, and at the same time enhances the mechanical and electrical properties of epoxy resin. The carbon nanotube / polyaniline composite modified epoxy resin conductive coating prepared by the present invention has better mechanical and electrical properties than traditional conductive coatings, and can be better applied to aerospace, batteries, communications, new energy and other aspects.
[0012] The first object of the present invention is to provide a method for preparing a carbon nanotube / polyaniline composite modified epoxy resin conductive coating, comprising the following steps:
[0013] (1) mixing carbon nanotubes and a solvent uniformly to obtain a uniformly dispersed carbon nanotube dispersion;
[0014] The solvent is one or more of m-cresol, o-cresol, p-cresol, and resorcinol; or a mixture of the above solvents and one or more of n-hexane, 1,4-dioxane, toluene, anisole, and chloroform;
[0015] (2) adding polyaniline to the carbon nanotube dispersion, mixing uniformly, and evaporating or purifying the solvent to obtain a carbon nanotube / polyaniline composite;
[0016] (3) adding the carbon nanotube / polyaniline composite to the epoxy resin and mixing them evenly to obtain a mixture; adding a curing agent to the mixture and mixing them evenly to obtain an epoxy resin conductive coating based on the carbon nanotube / polyaniline composite modification.
[0017] In one embodiment of the present invention, the carbon nanotubes in step (1) are multi-walled carbon nanotubes with an average diameter of 7-11 nm and a carbon nanotube length of 5-20 μm.
[0018] In one embodiment of the present invention, the mass concentration of carbon nanotubes in the carbon nanotube dispersion in step (1) is 0.1-2%.
[0019] In one embodiment of the present invention, the uniform mixing in step (1) is ultrasonic mixing, and the ultrasonic mixing is performed at 30-60W and 400-800rpm for 30-60min.
[0020] In one embodiment of the present invention, the mass ratio of the polyaniline in step (2) to the carbon nanotubes in step (1) is 10:(1-10), and more preferably 10:(1-5).
[0021] In one embodiment of the present invention, the uniform mixing in step (2) is ultrasonic mixing, and the ultrasonic mixing is performed at 30-60W and 400-800rpm for 30-60min.
[0022] In one embodiment of the present invention, the solvent purification in step (2) is to add a low dielectric constant solvent, and the volume ratio of the addition amount to the carbon nanotube dispersion is (0.1-1):1; the low dielectric constant solvent is one of acetone, ethanol, methanol, and butanone.
[0023] In one embodiment of the present invention, when polyaniline is added in step (2), an auxiliary dispersant may be added simultaneously, and the mass ratio of the auxiliary dispersant to polyaniline is 1-5:10;
[0024] The auxiliary dispersant is a phenolic hydroxyl dispersant; further, the phenolic hydroxyl dispersant is one or more of tannic acid, cardanol, and dopamine.
[0025] In one embodiment of the present invention, the mass concentration of the carbon nanotube / polyaniline composite in the epoxy resin conductive coating of step (3) is 0.1-5 wt %.
[0026] In one embodiment of the present invention, the uniform mixing in step (3) is carried out by stirring at 15-40° C. (normal temperature) and 300-600 rpm for 5-40 min.
[0027] In one embodiment of the present invention, the curing agent in step (3) is an epoxy curing agent.
[0028] In one embodiment of the present invention, the mass ratio of the curing agent to the epoxy resin in step (3) is 0.1-0.5:1.
[0029] The second object of the present invention is the epoxy resin conductive coating based on carbon nanotube / polyaniline composite modification prepared by the method of the present invention.
[0030] The third object of the present invention is to provide a conductive composite material, which adopts the carbon nanotube / polyaniline composite-modified epoxy resin conductive coating of the present invention.
[0031] In one embodiment of the present invention, the substrate of the conductive composite material is one of plastic, fiber and fabric.
[0032] In one embodiment of the present invention, the conductive composite material is prepared by coating the carbon nanotube / polyaniline composite modified epoxy resin conductive coating described in the present invention on the surface of a substrate and drying it.
[0033] In one embodiment of the present invention, after drying, the film formed by the coating is peeled off from the substrate to obtain a conductive composite material.
[0034] The fourth objective of the present invention is to apply the carbon nanotube / polyaniline composite-modified epoxy resin conductive coating and conductive composite material described in the present invention in the fields of aerospace, battery, communication and new energy.
[0035] The fifth object of the present invention is to provide a battery, which adopts the epoxy resin conductive coating and conductive composite material based on carbon nanotube / polyaniline composite modification described in the present invention.
[0036] A sixth object of the present invention is to provide a method for improving the dispersibility, stability and conductivity of carbon nanotubes in epoxy resin, comprising the following steps:
[0037] (1) mixing carbon nanotubes and a solvent uniformly to obtain a uniformly dispersed carbon nanotube dispersion;
[0038] The solvent is one or more of m-cresol, o-cresol, p-cresol, and resorcinol; or a mixture of the above solvents and one or more of n-hexane, 1,4-dioxane, toluene, anisole, and chloroform;
[0039] (2) adding polyaniline to the carbon nanotube dispersion, mixing uniformly, and evaporating or purifying the solvent to obtain a carbon nanotube / polyaniline composite;
[0040] (3) adding the carbon nanotube / polyaniline composite to the epoxy resin and mixing them evenly to obtain a mixture; adding a curing agent to the mixture and mixing them evenly to obtain an epoxy resin conductive coating based on the carbon nanotube / polyaniline composite modification.
[0041] [Beneficial Effects]
[0042] (1) The present invention uses a specific solvent to disperse carbon nanotubes, which greatly reduces the time and power of ultrasound, avoids destroying the structure of the carbon nanotubes themselves, and weakens the performance of the carbon nanotubes; so that the epoxy resin conductive coating based on carbon nanotube / polyaniline composite modification exhibits excellent conductive properties.
[0043] (2) The present invention uses polyaniline to further improve the dispersion performance of carbon nanotubes in a specific solvent, improve the compatibility of carbon nanotubes with epoxy resin, reduce the agglomeration of carbon nanotubes, and improve the interface interaction force.
[0044] (3) The present invention adopts a process of preliminarily untangling carbon nanotubes with a specific solvent and purifying the carbon nanotubes. The prepared carbon nanotube / polyaniline slurry is suitable for a solvent-free system, thus avoiding environmental pollution caused by solvent volatilization. At the same time, since purification is required, the specific solvent used can be recycled to some extent, thus improving resource utilization.
[0045] (4) The carbon nanotube / polyaniline composite prepared by the present invention has good dispersibility and good compatibility with other oily resins, and can be compounded with resins to prepare stable conductive coatings.
[0046] (5) The carbon nanotube / polyaniline composite modified epoxy resin conductive coating prepared by the present invention exhibits excellent conductive properties and mechanical properties, and has broad application prospects in the fields of new energy, aerospace, communications, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 (a) FT-IR image and (b) Raman spectrum of CNT, PANI, and CNT / PANI in Example 1.
[0048] Figure 2 (a) Thermogravimetric analysis diagrams of CNT, PANI, and CNT / PANI in Example 1 and (b) thermogravimetric analysis diagrams of different PANI addition amounts in Example 2.
[0049] Figure 3 Cross-sectional SEM images of composite films of (a) 0.5% EP / CNT, (b) 0.5% EP / original CNT, (c) 0.5% EP / (CNT-PANI=10-1), (d) 0.5% EP / (CNT-PANI=10-2), (e) a partial enlarged view of d, (f) a partial enlarged view of c, (g) 0.5% EP / (CNT-PANI=10-3), (h) 0.5% EP / (CNT-PANI=10-4), and (i) 0.5% EP / (CNT-PANI=10-5). DETAILED DESCRIPTION
[0050] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0051] Test method:
[0052] 1. Infrared test:
[0053] A Fourier transform infrared spectrometer (Nicolet iS50) produced by Thermo Fisher Scientific was used to test whether the preparation of carbon nanotubes / polyaniline was successful.
[0054] 2. Thermogravimetric test:
[0055] The adsorption amount of polyaniline in carbon nanotubes / polyaniline was tested using a Mettler-Toledo thermogravimetric analyzer (TGA2) produced by Mettler, Switzerland.
[0056] 3. Raman test:
[0057] The interaction force between carbon nanotubes and polyaniline was tested using a confocal Raman spectrometer (inVia) produced by Renishaw, UK.
[0058] 4. SEM test
[0059] The cross-section of the composite film was characterized using a field emission electron scanning microscope (S-4800) produced by Hitachi, Japan.
[0060] 5. Resistance:
[0061] Use a multimeter to test.
[0062] 6. Mechanical properties test
[0063] The mechanical properties of the composite film were tested using a universal testing machine (5967X) produced by Instron, USA. The sample specifications are dumbbell-shaped, with a length of 20 mm, a width of 4 mm, and a thickness of 0.4 mm.
[0064] The raw materials used in the embodiment:
[0065] Multi-walled carbon nanotubes: average diameter 7-11 nm, carbon tube length 5-20 μm, purchased from Jiangsu Tiannai Technology Co., Ltd. (FT7320 CNT);
[0066] Polyaniline powder: particle size 5-8 μm, sulfonic acid doped, conductive, purity >98%, purchased from Sigma-Aldrich;
[0067] Epoxy resin: Tianshi Technology Co., Ltd., TTC-518-3AWJ22C131;
[0068] Epoxy curing agent: Tianshi Technology Co., Ltd., TTC-518-3AWJ22C141;
[0069] m-Cresol: 99.5%;
[0070] In the examples, reactions without specific reference to reaction temperature were carried out at room temperature (25° C.).
[0071] Example 1
[0072] A method for preparing a carbon nanotube / polyaniline composite-modified epoxy resin conductive coating comprises the following steps:
[0073] (1) 0.15 g of multi-walled carbon nanotubes (CNTs) and 30 g of m-cresol were mixed, and ultrasonically mixed in a water bath at 40 W and 600 rpm for 60 min to obtain a uniformly dispersed carbon nanotube dispersion; wherein the mass concentration of the carbon nanotubes in the carbon nanotube dispersion was 0.5%;
[0074] (2) adding 0.03 g of polyaniline (PANI) to the carbon nanotube dispersion, mixing in a water bath ultrasonic manner at 40 W and 600 rpm for 10 min, adding acetone to allow the composite to settle, and preparing a carbon nanotube / polyaniline composite; wherein the volume ratio of acetone to the carbon nanotube dispersion is 0.5:1;
[0075] (3) Add 0.5 g of carbon nanotube / polyaniline composite to 100 g of epoxy resin (EP), stir at 500 rpm for 30 min to obtain a mixture; add 50 g of epoxy curing agent to the mixture, stir at 500 rpm for 10 min to obtain an epoxy resin conductive coating based on carbon nanotube / polyaniline composite modification, marked as 0.5% EP / (CNT-PANI=10-2).
[0076] Example 2
[0077] The mass of polyaniline (PANI) in step (2) of Example 1 was adjusted to 0.015 g, 0.045 g, 0.06 g, and 0.075 g, and the rest was consistent with Example 1 to obtain epoxy resin conductive coating, which was marked as 0.5% EP / (CNT-PANI=10-1), 0.5% EP / (CNT-PANI=10-3), 0.5% EP / (CNT-PANI=10-4), and 0.5% EP / (CNT-PANI=10-5).
[0078] Example 3
[0079] The addition amount of the carbon nanotube / polyaniline composite in step (3) of Example 1 was adjusted to 0.1 g, 1.0 g, and 1.5 g, and the rest was consistent with Example 1 to obtain epoxy resin conductive coatings, which were marked as 0.1% EP / (CNT-PANI=10-2), 1.0% EP / (CNT-PANI=10-2), and 1.5% EP / (CNT-PANI=10-2).
[0080] Comparative Example 1
[0081] The carbon nanotube / polyaniline composite in step (3) of Example 1 was omitted, and the rest of the steps were the same as in Example 1 to obtain a coating, which was marked as EP.
[0082] Comparative Example 2
[0083] The carbon nanotube / polyaniline composite in step (3) of Example 1 was adjusted to multi-walled carbon nanotubes, and the rest was kept consistent with Example 1 to obtain a coating marked as 0.5% EP / original CNT.
[0084] Comparative Example 3
[0085] The carbon nanotube / polyaniline composite in step (3) of Example 1 was adjusted to a multi-walled carbon nanotube slurry, and the rest was kept the same as Example 1 to obtain a coating, which was marked as 0.5% EP / CNT;
[0086] The preparation method of multi-walled carbon nanotube slurry is as follows:
[0087] 0.15 g of multi-walled carbon nanotubes (CNT) and 30 g of m-cresol were mixed, and ultrasonically mixed in a water bath at 40 W and 600 rpm for 60 min to obtain a uniformly dispersed carbon nanotube dispersion; wherein the mass concentration of the carbon nanotubes in the carbon nanotube dispersion was 0.5%;
[0088] Acetone was added to allow the composite to settle, thereby preparing a carbon nanotube slurry; wherein the volume ratio of acetone to the carbon nanotube dispersion was 0.5:1.
[0089] Example 4
[0090] A conductive composite material, which uses the coatings obtained in Examples 1-3 and Comparative Examples 1-3;
[0091] Specific;
[0092] The coatings obtained in Examples 1-3 and Comparative Examples 1-3 were scraped onto a PET film (thickness 40 μm) using a 750 μm four-sided preparation device, dried in an oven at 100° C. for 60 min, and then the film formed by the coating was peeled off the PET film to obtain a conductive composite material.
[0093] The obtained conductive composite material was subjected to performance testing, and the test results are as follows:
[0094] Figure 1 (a) FT-IR and (b) Raman spectra of CNT, PANI, and CNT / PANI in Example 1. Figure 1 In (a), we can see that compared with CNT, CNT / PANI has some characteristic peaks that CNT has never had, namely 1307cm -1 、1480cm -1 and 1575cm -1 The peaks correspond to the stretching vibrations of CN, C=C and C=N. These newly emerged peaks are the characteristic infrared peaks of PANI. Figure 1 It can be seen from (b) that the 1156cm -1 Move to 1166 cm in CNT / PANI -1 This indicates that the interaction between the quinone ring on PANI and the carbon ring on CNT in CNT / PANI is very significant, and the PANI-modified CNT is successfully prepared.
[0095] Figure 2 The thermogravimetric analysis diagrams of CNT, PANI, and CNT / PANI in Example 1 (a) and the thermogravimetric analysis diagrams of different PANI addition amounts in Example 2 (b). Figure 2 It can be seen that the thermal weight loss curve of CNT / PANI has an obvious pyrolysis weight loss phenomenon at 300-500℃, which is the same as the pyrolysis weight loss of PANI. This proves from the side that PANI is adsorbed on CNT and CNT / PANI is successfully prepared. Figure 2 The thermogravimetric curve of (b) is used to determine the residual amounts of CNT, CNT / PANI (10 / 1), CNT / PANI (10 / 2), CNT / PANI (10 / 3), CNT / PANI (10 / 4), and CNT / PANI (10 / 5) after heating to 800°C, which are 96.0%, 93.2%, 89.8%, 85.9%, 83.4%, and 80.9%, respectively. Based on the residual amount of PANI, it can be seen that the actual adsorption amount of PANI is much less than the added amount, and the actual adsorption amount is about 3%, 7%, 10%, 13%, and 16% according to the added amount.
[0096] Figure 3Cross-sectional SEM images of composite films of (a) 0.5% EP / CNT, (b) 0.5% EP / original CNT, (c) 0.5% EP / (CNT-PANI=10-1), (d) 0.5% EP / (CNT-PANI=10-2), (e) a partial enlarged view of d, (f) a partial enlarged view of c, (g) 0.5% EP / (CNT-PANI=10-3), (h) 0.5% EP / (CNT-PANI=10-4), (i) 0.5% EP / (CNT-PANI=10-5). Used to observe the dispersion degree and interface effect of CNT / PANI in the two-component epoxy resin matrix. Figure 3 It can be seen that: when comparing 0.5% EP / CNT with 0.5% EP / original CNT, the original CNT has not been dispersed, and its agglomeration phenomenon is more obvious, and the agglomeration area is larger. When the amount of CNT added is kept at 0.5%, different amounts of PANI are added. As the amount of PANI increases, the dispersion effect of CNT in the EP matrix is significantly improved. When the amount of PANI added is 10% of CNT, CNT still has a small amount of agglomeration, but the agglomeration phenomenon is significantly weakened. As the amount of PANI added increases, the agglomeration phenomenon of CNT in the matrix completely disappears at 20%, and the dispersion of CNT in the matrix is greatly improved. The CNT is completely coated with PANI, and the cross-section of the composite film is relatively smooth, indicating that the compatibility between CNT and EP is good at a high PANI ratio.
[0097] Table 1 Mechanical properties test results
[0098]
[0099] Table 2 Conductivity test
[0100]
[0101]
[0102] Note: “-” means the resistance is very large and it has no conductive properties.
[0103] Example 5
[0104] The intermediate cresol in step (1) of Example 1 was adjusted to a mixed solvent of 1,4-dioxane and meta-cresol in a volume ratio of 1:4; the rest was kept consistent with Example 1 to obtain a conductive coating.
[0105] Example 6
[0106] The intermediate cresol in step (1) of Example 1 was adjusted to a mixed solvent of resorcinol and meta-cresol in a volume ratio of 1:4; the rest was kept consistent with Example 1 to obtain a conductive coating.
[0107] Example 7
[0108] The acetone in step (2) of Example 1 was adjusted to ethanol; the rest was kept the same as Example 1 to obtain a conductive coating.
[0109] Comparative Example 4
[0110] The polyaniline in Example 1 was adjusted to polyvinyl pyrrolidone, and the other parts were kept the same as in Example 1 to obtain a conductive coating.
[0111] Comparative Example 5
[0112] The polyaniline in Example 1 was adjusted to gallic acid, and the other contents were kept the same as in Example 1 to obtain a conductive coating.
[0113] Comparative Example 6
[0114] The acetone in step (2) of Example 1 was adjusted to a 4% by mass NaOH aqueous solution; the rest was kept the same as Example 1 to obtain a conductive coating.
[0115] Comparative Example 7
[0116] The acetone in step (2) of Example 1 was adjusted to N-methylpyrrolidone (NMP); the other conditions were kept the same as in Example 1 to obtain a conductive coating.
[0117] Example 8
[0118] A conductive composite material, which uses the coatings obtained in Examples 5-7 and Comparative Examples 4-7;
[0119] Specific;
[0120] The coatings obtained in Examples 5-7 and Comparative Examples 4-7 were scraped onto a PET film (thickness 40 μm) using a 750 μm four-sided preparation device, dried in an oven at 100° C. for 60 min, and then the film formed by the coating was peeled off the PET film to obtain a conductive composite material.
[0121] The obtained conductive composite material was subjected to performance testing, and the test results are as follows:
[0122] Table 3 Test results of Examples 5-7
[0123] example Tensile strength(MPa) Elongation at break (%) Surface resistance(Ω) / sq Example 5 44.81±0.5 8.24±0.7 <![CDATA[4.7×10 7 ]]> Example 6 46.54±0.6 8.85±0.5 <![CDATA[8.8×10 6 ]]> Example 7 42.36±0.5 6.74±0.5 <![CDATA[6.8×10 6 ]]>
[0124] Table 4 Test results of comparative examples 4-7
[0125] example Surface resistance(Ω) / sq Comparative Example 4 <![CDATA[10 8 ]]> Comparative Example 5 <![CDATA[10 8 ]]> Comparative Example 6 <![CDATA[10 9 ]]> Comparative Example 7 <![CDATA[5.2×10 7 ]]>
[0126] Comparative Example 8
[0127] A method for preparing epoxy resin conductive coating comprises the following steps:
[0128] (1) 0.15 g of multi-walled carbon nanotubes (CNT), 0.03 g of polyaniline (PANI) and 30 g of m-cresol were mixed, and ultrasonically mixed in a water bath at 40 W and 600 rpm for 60 min to obtain a uniformly dispersed mixed solution;
[0129] (2) adding acetone to allow the composite to settle, thereby preparing a carbon nanotube / polyaniline composite; wherein the volume ratio of acetone to the mixed solution is 0.5:1;
[0130] (3) Add 0.5 g of carbon nanotube / polyaniline composite to 100 g of epoxy resin (EP), stir at 500 rpm for 30 min to obtain a mixture; add 50 g of epoxy curing agent to the mixture, stir at 500 rpm for 10 min to obtain an epoxy resin conductive coating based on carbon nanotube / polyaniline composite modification.
[0131] turn out:
[0132] Multi-walled carbon nanotubes (CNTs) are severely aggregated and cannot form a uniform system.
[0133] Comparative Example 9
[0134] A method for preparing epoxy resin conductive coating comprises the following steps:
[0135] (1) 0.03 g of polyaniline (PANI) 0 and 30 g of m-cresol were mixed, and ultrasonically mixed in a water bath at 40 W and 600 rpm for 60 min to obtain a uniformly dispersed polyaniline dispersion;
[0136] (2) adding 0.15 g of multi-walled carbon nanotubes (CNT) to the polyaniline dispersion, mixing in a water bath ultrasonic manner at 40 W and 600 rpm for 10 min, adding acetone to allow the composite to settle, and preparing a carbon nanotube / polyaniline composite; wherein the volume ratio of acetone to the polyaniline dispersion is 0.5:1;
[0137] (3) Add 0.5 g of carbon nanotube / polyaniline composite to 100 g of epoxy resin (EP), stir at 500 rpm for 30 min to obtain a mixture; add 50 g of epoxy curing agent to the mixture, stir at 500 rpm for 10 min to obtain an epoxy resin conductive coating based on carbon nanotube / polyaniline composite modification.
[0138] turn out:
[0139] Multi-walled carbon nanotubes (CNTs) are severely aggregated and cannot form a uniform system.
[0140] Example 8
[0141] A method for preparing a carbon nanotube / polyaniline composite-modified epoxy resin conductive coating comprises the following steps:
[0142] (1) 0.15 g of multi-walled carbon nanotubes (CNTs) and 30 g of m-cresol were mixed, and ultrasonically mixed in a water bath at 40 W and 600 rpm for 60 min to obtain a uniformly dispersed carbon nanotube dispersion; wherein the mass concentration of the carbon nanotubes in the carbon nanotube dispersion was 0.5%;
[0143] (2) adding 0.03 g of polyaniline (PANI) and 0.01 g of tannic acid to the carbon nanotube dispersion, mixing them in a water bath ultrasonically at 40 W and 600 rpm for 10 min, adding acetone to allow the composite to settle, and preparing a carbon nanotube / polyaniline composite; wherein the volume ratio of acetone to the carbon nanotube dispersion is 0.5:1;
[0144] (3) Add 0.5 g of carbon nanotube / polyaniline composite to 100 g of epoxy resin (EP), stir at 500 rpm for 30 min to obtain a mixture; add 50 g of epoxy curing agent to the mixture, stir at 500 rpm for 10 min to obtain an epoxy resin conductive coating based on carbon nanotube / polyaniline composite modification.
[0145] Example 9
[0146] A method for preparing a carbon nanotube / polyaniline composite-modified epoxy resin conductive coating comprises the following steps:
[0147] (1) 0.15 g of multi-walled carbon nanotubes (CNTs) and 30 g of m-cresol were mixed, and ultrasonically mixed in a water bath at 40 W and 600 rpm for 60 min to obtain a uniformly dispersed carbon nanotube dispersion; wherein the mass concentration of the carbon nanotubes in the carbon nanotube dispersion was 0.5%;
[0148] (2) adding 0.03 g of polyaniline (PANI) and 0.01 g of cardanol to the carbon nanotube dispersion, mixing them in a water bath ultrasonically at 40 W and 600 rpm for 10 min, adding acetone to allow the composite to settle, and preparing a carbon nanotube / polyaniline composite; wherein the volume ratio of acetone to the carbon nanotube dispersion is 0.5:1;
[0149] (3) Add 0.5 g of carbon nanotube / polyaniline composite to 100 g of epoxy resin (EP), stir at 500 rpm for 30 min to obtain a mixture; add 50 g of epoxy curing agent to the mixture, stir at 500 rpm for 10 min to obtain an epoxy resin conductive coating based on carbon nanotube / polyaniline composite modification.
[0150] The obtained epoxy resin conductive coating was subjected to performance testing, and the specific testing method is as follows:
[0151] The coatings obtained in Examples 8 and 9 were scraped onto a PET film (thickness 40 μm) using a 750 μm four-sided preparation device, and dried in an oven at 100° C. for 60 min. The film formed by the coatings was then peeled off the PET film to obtain a conductive composite material.
[0152] The test results of the conductive composite material are as follows:
[0153] Table 5 Test results of Examples 8 and 9
[0154] example Tensile strength(MPa) Elongation at break (%) Surface resistance(Ω) / sq Example 8 48.36±0.8 11.84±0.4 <![CDATA[5.8×10 6 ]]> Example 9 49.50±0.6 12.44±0.5 <![CDATA[4.6×10 6 ]]>
[0155] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a carbon nanotube / polyaniline composite modified epoxy resin conductive coating, characterized in that: The steps include: (1) mixing carbon nanotubes and a solvent uniformly to obtain a uniformly dispersed carbon nanotube dispersion; The solvent is one or more of m-cresol, o-cresol, p-cresol, and resorcinol; or a mixture of the above solvents and one or more of n-hexane, 1,4-dioxane, toluene, anisole, and chloroform; (2) adding polyaniline to the carbon nanotube dispersion, mixing uniformly, and evaporating or purifying the solvent to obtain a carbon nanotube / polyaniline composite; (3) adding the carbon nanotube / polyaniline composite to the epoxy resin and mixing them evenly to obtain a mixture; adding a curing agent to the mixture and mixing them evenly to obtain an epoxy resin conductive coating based on the carbon nanotube / polyaniline composite modification.
2. The method according to claim 1, characterized in that The mass concentration of carbon nanotubes in the carbon nanotube dispersion of step (1) is 0.1-2%; the mass ratio of polyaniline in step (2) to the carbon nanotubes in step (1) is 10:(1-10).
3. The method according to claim 1, characterized in that In step (2), the solvent purification is to add a low dielectric constant solvent, wherein the volume ratio of the added amount to the carbon nanotube dispersion is (0.1-1):1; the low dielectric constant solvent is one of acetone, ethanol, methanol and butanone.
4. The method according to claim 1, characterized in that: The mass concentration of the carbon nanotube / polyaniline composite in the epoxy resin conductive coating of step (3) is 0.1-5wt%.
5. The method according to claim 1, characterized in that When polyaniline is added in step (2), an auxiliary dispersant may be added simultaneously, and the auxiliary dispersant is a phenolic hydroxyl dispersant.
6. The carbon nanotube / polyaniline composite modified epoxy resin conductive coating prepared by the method according to any one of claims 1 to 5.
7. A conductive composite material, characterized in that: The carbon nanotube / polyaniline composite-modified epoxy resin conductive coating according to claim 6 is used.
8. Application of the carbon nanotube / polyaniline composite-modified epoxy resin conductive coating according to claim 6 and the conductive composite material according to claim 7 in the fields of aerospace, batteries, communications, and new energy.
9. A battery, characterized in that: The carbon nanotube / polyaniline composite-modified epoxy resin conductive coating according to claim 6 and the conductive composite material according to claim 7 are used.
10. A method for improving the dispersibility, stability and conductivity of carbon nanotubes in epoxy resin, characterized in that: The steps include: (1) mixing carbon nanotubes and a solvent uniformly to obtain a uniformly dispersed carbon nanotube dispersion; The solvent is one or more of m-cresol, o-cresol, p-cresol, and resorcinol; or a mixture of the above solvents and one or more of n-hexane, 1,4-dioxane, toluene, anisole, and chloroform; (2) adding polyaniline to the carbon nanotube dispersion, mixing uniformly, and evaporating or purifying the solvent to obtain a carbon nanotube / polyaniline composite; (3) adding the carbon nanotube / polyaniline composite to the epoxy resin and mixing them evenly to obtain a mixture; adding a curing agent to the mixture and mixing them evenly to obtain an epoxy resin conductive coating based on the carbon nanotube / polyaniline composite modification.
Citation Information
Patent Citations
Method for obtaining high-performance polyaniline base thermoelectric materials
CN103137848A
Carbon nanotube / polyaniline composite material and preparation method thereof
CN110563973A
Preparation and application of water-based graphene / carbon nanotube composite hybrid
CN117819535A
Preparation and application of water-based graphene oxide / polyaniline composite hybrid
CN117820859A
Method of making organic transparent electrode fordisplay
KR1020050001589A
Cited By
Anti-static corrosion-resistant epoxy coating and preparation method thereof
CN120904756A
A high-concentration carbon nanotube water-based epoxy composite coating with a hydrophobic shell layer constructed by tannic acid and a preparation method thereof
CN122628631A